(untitled) (The South Asianist Journal, 2013)
This two-day symposium brought together an international array of senior and junior researchers from across the natural sciences, the humanities, and the social sciences for an interdisciplinary exploration of the manifold aspects of the human-elephant relationship. Hosted by the Department of Anthropology and the New Zealand South Asia Centre (NZSAC), anthropologists, ecologists, geographers, historians, political scientists, Sanskritists, zoologists, and zoo elephant experts from Australia, France, Germany, India, New Zealand, Sri Lanka, the UK, and the USA met for an intensive meeting featuring dynamic presentations and vibrant discussion. The event provided a unique opportunity for productive debate across disciplinary boundaries on issues of welfare and conservation, history and coexistence, policy and practice, through which elephants have been variously bound up in human projects as weapons of war, emblems of prestige, symbols of divinity, objects of entertainment, icons of conservation, commodities for exchange, vehicles for labour, and intimate companions.